Mastering SQL server 2014 data mining : master selecting, applying, and deploying data mining models to build powerful predictive analysis frameworks /: master selecting, applying, and deploying data mining models to build powerful predictive analysis frameworks. (2014) - Bassan, Amarpreet Singh; Sarkar, Debarchan
No abstract available